Effect of process parameters on microstructure and mechanical properties of a nickel-aluminum-bronze alloy fabricated by laser powder bed fusion - Han, Chang-Jun (2025)
This work investigated the effect of process parameters on densification, microstructure, and mechanical properties of a nickel-aluminum-bronze (NAB) alloy fabricated by laser powder bed fusion (LPBF) additive manufacturing. The LPBF-printed NAB alloy samples with relative densities of over 98.5% were obtained under the volumetric energy density range of 200–250 J/mm3. The microstructure of the NAB alloy printed in both horizontal and vertical planes primarily consisted of β′ martensitic phase and banded α phase. In particular, a coarser-columnar grain structure and stronger crystallographic texture were achieved in the vertical plane, where the maximum texture intensity was 30.56 times greater than that of random textures at the (100) plane. Increasing the volumetric energy density resulted in a decrease in the columnar grain size, while increasing the amount of α phase. Notably, β1′ martensitic structures with nanotwins and nanoscale κ-phase precipitates were identified in the microstructure of LPBF-printed NAB samples with a volumetric energy density of 250 J/mm3. Furthermore, under optimal process parameters with a laser power of 350 W and scanning speed of 800 mm/s, significant improvements were observed in the microhardness (HV 386) and ultimate tensile strength (671 MPa), which was attributed to an increase in refined acicular martensite.